1996
DOI: 10.1021/ja954096m
|View full text |Cite
|
Sign up to set email alerts
|

Valence Electron Cloud Asymmetry from Two Points of View:  A Correlation between Mössbauer Quadrupole Splittings and 57Fe NMR Chemical Shifts of Diamagnetic Iron(II) Porphyrinates

Abstract: We have prepared a series of 94.5%-enriched 57 Fe(II) complexes of tetramesitylporphyrin and octaethylporphyrin having various bis-or mixed axial ligation and investigated them by both NMR and Mo ¨ssbauer spectroscopy. The results obtained, and literature values for MbCO and cytochrome c, show a rough correlation between ∆E Q and δ Fe . This correlation suggested that the previously-reported chemical shifts of the complexes [TPPFeL 2 ], L ) pyridine-d 5 , and pyrrolidine (Nozawa, T.; Sato, M.; Hatano, M.; Koba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
3
29
0
1
Order By: Relevance
“…At 250 K, the 57 Fe Mössbauer spectrum of solid 2 shows a high-spin Fe­(II) species comprising 46(5)% of the sample with an isomer shift (δ) of 0.880(9) mm/s and quadrupole splitting (Δ E Q ) of 3.22(2) mm/s (Figure A, green). , The remaining sample has a broad, poorly resolved signal (blue) potentially composed of multiple sites with an δ of 0.23(2) mm/s and Δ E Q of 0.81(2) mm/s which we assign as low-spin Fe­(II) sites. These parameters are outside of the typical ranges for both low-spin Fe­(II) (δ: 0.36–0.52 mm/s; Δ E Q : 0.23–0.52 mm/s) and low-spin Fe­(III) (δ: 0.20–0.28 mm/s; Δ E Q : 1.5–1.7 mm/s) reported for TPA ligated 6-coordinate complexes but are similar to other low-spin Fe­(II) species …”
Section: Results and Discussionsupporting
confidence: 43%
“…At 250 K, the 57 Fe Mössbauer spectrum of solid 2 shows a high-spin Fe­(II) species comprising 46(5)% of the sample with an isomer shift (δ) of 0.880(9) mm/s and quadrupole splitting (Δ E Q ) of 3.22(2) mm/s (Figure A, green). , The remaining sample has a broad, poorly resolved signal (blue) potentially composed of multiple sites with an δ of 0.23(2) mm/s and Δ E Q of 0.81(2) mm/s which we assign as low-spin Fe­(II) sites. These parameters are outside of the typical ranges for both low-spin Fe­(II) (δ: 0.36–0.52 mm/s; Δ E Q : 0.23–0.52 mm/s) and low-spin Fe­(III) (δ: 0.20–0.28 mm/s; Δ E Q : 1.5–1.7 mm/s) reported for TPA ligated 6-coordinate complexes but are similar to other low-spin Fe­(II) species …”
Section: Results and Discussionsupporting
confidence: 43%
“…The 57 Fe chemical shift tensor orientations were generally close to molecular symmetry axes, although reversed from previous work, but with the skew of the shielding tensor again reversing sign on transition from strong to weak ligand fields. Also, the results showed that the paramagnetic contribution overwhelmingly dominated the total absolute shielding, as noted in previous work [70]. Interestingly, when MbCO models having distorted Fe-C-O geometries (as seen in protein X-ray crystal structures) were employed, the experimental 57 Fe chemical shifts were in poor accord with the theoretical results.…”
Section: Dft Investigation Of Metal Ion Nmr and 57 Fe Mö Ssbauer Quadsupporting
confidence: 48%
“…For example, six-coordinate Fe(II/III) heme complexes with imidazole (Im) and pyridine have been extensively characterized by X-ray crystallography,14 computational methods15 and spectroscopy16. In contrast, only limited data have been reported for alkylamine-ligated iron(III) porphyrins.…”
Section: Introductionmentioning
confidence: 99%